Human chemosignals of disgust facilitate food judgment. Issue 1 (December 2018) - Zheng, Yan; You, Yuqi; Farias, Ana; Simon, Jessica; Semin, Gün; Smeets, Monique; Li, Wen
Abstract Choosing food is not a trivial decision that people need to make daily, which is often subject to social influences. Here, we studied a human homolog of social transmission of food preference (STFP) as observed in rodents and other animals via chemosignals of body secretions. Human social chemosignals (sweat) produced during a disgust or neutral state among a group of donors were presented to participants undergoing a 2-alternative-forced-choice food healthiness judgment task during functional magnetic resonance imaging (fMRI). Response speed and two key signal detection indices—d' (discrimination sensitivity) andβ (response bias)—converged to indicate that social chemosignals of disgust facilitated food healthiness decisions, in contrast to primary disgust elicitors (disgust odors) that impaired the judgment. fMRI analyses (disgust vs. neutral sweat) revealed that the fusiform face area (FFA), amygdala, and orbitofrontal cortex (OFC) were engaged in processing social chemosignals of disgust during food judgment. Importantly, a double contrast of social signaling across modalities (olfactory vs. visual—facial expressions) indicated that the FFA and OFC exhibited preferential response to social chemosignals of disgust. Together, our findings provide initial evidence for human STFP, where social chemosignals are incorporated into food decisions by engaging social and emotional areas of the brain.